33.2k views
1 vote
What is the product of (a + 3)(a - 2)

User Xeen
by
5.4k points

2 Answers

5 votes

Answer:


\large\boxed{(a+3)(a-2)=a^2+a-6}

Explanation:

Use FOIL: (a + b)(c + d) = ac + ad + bc + bd


(a+3)(a-2)=(a)(a)+(a)(-2)+(3)(a)+(3)(-2)\\\\=a^2-2a+3a-6\qquad\text{combine like terms}\\\\=a^2+a-6

User Martin Janiczek
by
4.3k points
6 votes

Answer:
a^2+a-6

Explanation:

To solve the exercise you must apply the following proccedure:

- Apply the distributive property.

- Keepn on mind that when you multiply two powers with equal base, you must add the exponents.

- Add like terms.

Then:


(a)(a)-(a)(2)+(3)(a)-(3)(2)=a^2-2a+3a-6=a^2+a-6

User Vinay Joseph
by
5.4k points